RARE-13. CHARACTERISTICS AND TREATMENT PATTERNS IN CHILDREN WITH NEUROFIBROMATOSIS TYPE 1 (NF1) AND PLEXIFORM NEUROFIBROMAS (PN): A CROSS-SECTIONAL ANALYSIS OF CHILDREN'S TUMOR FOUNDATION (CTF) REGISTRY DATA. (11th November 2019) - He, Jinghua; Anne Pinto, Cathy; Yang, Xiaoqin; Diede, Scott; Deitz, Anne
Abstract: BACKGROUND: NF1-related PN can cause substantial morbidity, with no currently approved drug treatment available for PN treatment. Although surgery is the standard of care, complete resection of PN is often difficult due to encasement of vital structures and invasive and extensive PN growth. With limited real-world data among children with NF1-related PN, the study objectives were to describe the demographic, clinical characteristics, and treatment of these children. METHODS: A cross-sectional analysis of existing CTF web-based, patient-entered, registry data collected between 2012–2018 was conducted. To be included in analysis, patients had to complete at least one registry survey, and be ≤ 19 years of age at the time of first survey completion, with patient- or parent/ guardian reported diagnosis of NF1 and at least 1 PN. Descriptive statistical analysis was conducted on data collected from the first survey for each patient, to describe patient characteristics and treatment patterns. Results were stratified by region (US, ex-US). RESULTS: The sample included 943 pediatric patients (n=750 US, n=193 ex-US). The majority (85.9%) were less than 5 years of age at NF1 diagnosis (US: 87.6%; ex-US: 79.3%). Approximately half were male, and half reported more than 1 PN. The most common PN site include head (15.1%) and neck (12.6%). More than half of patients received no treatment (53.1%) for their PN. The most common treatments reported for PN were surgery (27.0%) and chemotherapy or drug therapy (10.0%). These results were generally consistent across regions. A malignant peripheral nerve sheath tumor (MPNST) and optic glioma (OG) were diagnosed in 21 (2.2%) and 308 (32.7%) patients, respectively; a large proportion of OG patients remained untreated (57.5%). Too few ex-US patients were available for detailed regional analysis. CONCLUSIONS: This study demonstrated that a large proportion of children diagnosed with NF1-related PN remain untreated, highlighting a substantial unmet need.